2008
DOI: 10.1148/radiol.2493072045
|View full text |Cite
|
Sign up to set email alerts
|

Parotid Gland Tumors: Can Addition of Diffusion-weighted MR Imaging to Dynamic Contrast-enhanced MR Imaging Improve Diagnostic Accuracy in Characterization?

Abstract: A persistent or flat TIC pattern on dynamic contrast-enhanced MR images indicates benign disease, but there is added value from including the ADC value in the evaluation of tumors that show a plateau or washout TIC pattern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
183
3
12

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 241 publications
(202 citation statements)
references
References 16 publications
4
183
3
12
Order By: Relevance
“…In this regard, multiparametric MR imaging was reported to be effective in differentiating benign and malignant salivary gland tumors. 12,20 Therefore, a combined use of diffusion-weighted and dynamic CE MR imaging may improve the diagnostic accuracy of differentiating benign lesions from malignant tumors in the sinonasal area. To facilitate this, a recently developed MR imaging factor-analysis technique, which is also based on the pixel-by-pixel analysis of TIC patterns, would be useful 21,22 ; the 2D analysis of the TIC profiles (MR imaging factor analysis) and ADC maps may enable the pixel-by-pixel evaluation of contrast enhancement kinetics and ADCs in sinonasal tumors and tumorlike lesions.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, multiparametric MR imaging was reported to be effective in differentiating benign and malignant salivary gland tumors. 12,20 Therefore, a combined use of diffusion-weighted and dynamic CE MR imaging may improve the diagnostic accuracy of differentiating benign lesions from malignant tumors in the sinonasal area. To facilitate this, a recently developed MR imaging factor-analysis technique, which is also based on the pixel-by-pixel analysis of TIC patterns, would be useful 21,22 ; the 2D analysis of the TIC profiles (MR imaging factor analysis) and ADC maps may enable the pixel-by-pixel evaluation of contrast enhancement kinetics and ADCs in sinonasal tumors and tumorlike lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Many earlier studies employing ADC measurement have used the linear regression model and various sets of gradient b factors [6][7][8][9][10][11][12][13][14][15][16]18,19 . This model was also applied in this study, and three sets of gradient b factors (0 and 1000 sec/mm 2 , 500 and 1000 sec/mm 2 , and all b factors for WLR fit) were compared.…”
Section: Discussionmentioning
confidence: 99%
“…One method of evaluating DWI is to measure the apparent diffusion coefficient (ADC), and several researchers have reported the usefulness of this technique in the evaluation of head and neck lesions [7][8][9][10][11][12][13][14][15][16][17][18][19] . The ADC can be useful in characterizing both normal and pathological tissue as it reflects microscopic water diffusion and tissue perfusion in biologic tissues [2][3][4][5] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, some authors postulated that these two types of lesions should be distinguished on the basis of their ADC values determined on diffusion-weighted MRI. Previous studies identified two cut-off values for ADC providing optimum accuracy in the differential diagnostics of pleomorphic adenomas and parotid malignancies: 1.4 × 10 3 mm 2 /s and 1.8 × 10 3 mm 2 /s [5,22].…”
Section: Discussionmentioning
confidence: 99%